Khat Dependency and Psychophysical Symptoms among Chewers in Jazan Region, Kingdom of Saudi Arabia. (28th February 2016) - El-Setouhy, Maged; Alsanosy, Rashad M.; Alsharqi, Abdallah; Ismail, Ahmed A.
Abstract : Background . Khat chewing is highly prevalent in Africa, Yemen and Jazan region, southwest of Saudi Arabia. Most of Jazani Khat chewers consider khat session as a social activity and do not consider khat dependency. The aim of this study was to explore khat dependency and its relationship with the psychophysical symptoms among chewers. Methods . Cross-sectional study on seventy Saudi male khat chewers living in Jazan area. Psychological dependence to khat chewing was evaluated using the Severity of Dependency Scale (SDS). The participants filled in a self-administrated assisted structured questionnaire designed to collect data about their medical history, neurological symptoms, and their chewing behavior. Results . Half (52.2%) of khat chewers showed psychological dependency. Those having longer khat sessions (≥6 hours) were more liable for dependency. Physical and psychological symptoms were more prevalent among khat dependent chewers. Conclusions . khat has a psychological dependence effect that can be measured by the SDS, even in low doses and with irregular use. SDS scale is a useful tool to expect the burden of either physical or psychological symptoms on khat chewers.